Rescue Cervical Cerclage for Protruding Amniotic Sac: A Retrospective Analysis of Clinical Efficacy - I-Le Hsu; Wei-Yun Hsu; Shih-Han Wang; Chin-Ru Ker; Te-Fu Chan (IMR Press, 2022)
Background: Cervical insufficiency, or cervical incompetence, describes the condition in which the cervix dilates without painful uterine contractions in the second trimester of pregnancy. It often leads to loss of pregnancy or preterm delivery. Recommendations for the prophylactic placement of cervical sutures are well established, however rescue cervical cerclage for a prolapsing amniotic bag is more controversial due to higher technical demands, higher risk of iatrogenic rupture of membranes, and questionable long-term neonatal prognosis. This study aimed to answer two important questions: (1) Should rescue cerclage be performed for those with an evidently protruding amniotic bag? (2) Who would benefit the most from rescue cerclage? Materials: Eighteen pregnant women with cervical incompetence with a clinically evident prolapsing amniotic bag from January 2016 to February 2020 were included. Four received conservative treatment, i.e., without cerclage, and the other 14 patients opted to receive emergency rescue cervical cerclage. Results: We classified the patients into futile (n = 7) and successful (n = 7) cerclage groups at post-operative day 21. Pregnancy and neonatal outcomes were obviously better in the success group, however no significant pre-operative predictive factors for success could be identified. The results of the women who did not receive cerclage and those with futile cerclage were comparable. Rescue cerclage was especially beneficial for those at 22 weeks to 26 weeks of gestation. Conclusions: The maternal and fetal outcomes of the patients with futile rescue cerclage were comparable to those who did not receive cerclage. Therefore, rescue cerclage for advanced cervical insufficiency could be considered, especially for those at 22 weeks to 26 weeks of gestation.